The Effect of Price Perception and Product Quality on Repurchase Intention: The Mediating Role of Customer Satisfaction among Oriflame Sun Care Consumers in Bandung City - Fachrani Saputra, Adinda; Evangalista Marliani, Leni (International Journal of Management Science and Information Technology, 2026)
The increasing competition in Indonesia’s skincare industry has heightened the need to understand the factors influencing consumers repurchase intention. This study examines the effects of price perception and product quality on repurchase intention, with customer satisfaction as a mediating variable among Oriflame Sun Care consumers in Bandung City. A quantitative approach was employed using convenience sampling, involving 127 consumers who had previously purchased and used Oriflame Sun Care products. Data were analyzed using multiple regression and the Sobel test. The results show that price perception and product quality have positive and significant effects on customer satisfaction. Price perception, product quality, and customer satisfaction also have positive and significant effects on repurchase intention. Furthermore, customer satisfaction significantly mediates the effects of both price perception and product quality on repurchase intention. These findings indicate that strengthening perceived price fairness, maintaining product quality, and improving customer satisfaction are important strategies for increasing repurchase intention among Oriflame Sun Care consumers.